Canine hip dysplasia treated by juvenile pubic symphysiodesis - Dueland, R. T.; Adams, W. M.; Patricelli, A. J.; Linn, K. A.; Crump, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
Objectives: To measure one and two year effects of juvenile pubic symphysiodesis (JPS) in puppies defined as ‘at-risk’ for canine hip dysplasia (CHD) using the following objective hip conformation criteria: Acetabular angle (AA), dorsal acetabular rim angle (DARA) and hip laxity (PennHIP© distraction index (DI).Design: Controlled clinical case study. Animals: Thirty-nine dysplastic puppies (six controls).Procedures: The dogs were anaesthetised and acetabular angle, DARA, and DI values were obtained by computed tomography and radiography preoperatively. Electro-cautery fusion of the pubic symphysis was performed between 12 – 24 weeks of age. The imaging was repeated at one and two years of age.Results: Significant hip improvements were seen at the two-year follow-up appointments for: AA (JPS dogs 31% increase, control 3%), DARA (JPS 38% decrease, control 15%) and DI (JPS 41% decrease in laxity, controls 20%) for all postoperative versus preoperative values. Pubic fusion occurred with minor morbidity.Conclusion: Juvenile pubic symphysiodesis resulted in significant improvements in hip conformation (AA and DARA), especially in mild to moderately lax hips (DI = 0.40–0.69). Most dogs with DI ≥0.70 increased in osteoarthritis grade by two years of age.Clinical relevance: Juvenile pubic symphysiodesis surgery at 12–24 weeks of age significantly improved hip conformation and decreased laxity in at-risk CHD dogs. Early-age (12 to 16 week) recognition of hip laxity offered greater JPS benefits than surgery performed at 19- to 24-weeks-old. Dogs with severe laxity (DI ≥0.70) continued to increase in osteoarthritis. An early (12–16 weeks) positive laxity test (Ortolani) should alert one to obtain objective laxity determinations (Penn-HIP© DI).
Keywords: Canine; hip dysplasia; juvenile pubic symphysiodesis